(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Women in our society serve a variety of roles. They generally handle a number of tasks at once. As a result, they are more likely to develop occupational disorders, which are further worsened by social, psychological, and physical problems. About one in 300 females suffers from an occupational ailment, and every year, such kind of cases are added to the current instances. This unnecessary illness is caused by a lack of occupational environment It is becoming abundantly evident that women's workplace requires special attention for a number of interconnected reasons. The biological, emotional, and health care demands of women are proportionately greater because they are responsible for more duties such as the majority of household work, caring for the young, elderly, and sick, household duties, and labour at the place of employment. Pregnancy and breastfeeding provide a real health risk at the workplace and call for safety precautions, particularly in light of chemically induced teratogenicity. The selection of employees and the provision of safe working conditions are important functions of a successful organization in order to enhance and sustain productivity and effectiveness while lowering absenteeism and turnover. In this article the author has tried to make a comparative analysis of occupational profile of women working in private and public sector of hospital on the basis various variables like growth , work place environment, opportunities available, coordination among management and employees, work pressure, resources available, employees behaviour about work pressure and task etc. on the basis of these variable author has tried to find out that whether they are satisfied with their occupational profile in healthcare sector or not.